Strongly reduced volumes of putamen and thalamus in Alzheimer's disease: an MRI study. - de Jong LW; van der Hiele K; Veer IM; Houwing JJ; Westendorp RG; Bollen EL; de Bruin PW; Middelkoop HA; van Buchem MA; van der Grond J; de Jong, L W; van der Hiele, K; et al. (Brain: A Journal of Neurology, 2008)
Atrophy is regarded a sensitive marker of neurodegenerative pathology. In addition to confirming the well-known presence of decreased global grey matter and hippocampal volumes in Alzheimer's disease, this study investigated whether deep grey matter structure also suffer degeneration in Alzheimer's disease, and whether such degeneration is associated with cognitive deterioration. In this cross-sectional correlation study, two groups were compared on volumes of seven subcortical regions: 70 memory complainers (MCs) and 69 subjects diagnosed with probable Alzheimer's disease. Using 3T 3D T1 MR images, volumes of nucleus accumbens, amygdala, caudate nucleus, hippocampus, pallidum, putamen and thalamus were automatically calculated by the FMRIB's Integrated Registration and Segmentation Tool (FIRST)--algorithm FMRIB's Software Library (FSL). Subsequently, the volumes of the different regions were correlated with cognitive test results. In addition to finding the expected association between hippocampal atrophy and cognitive decline in Alzheimer's disease, volumes of putamen and thalamus were significantly reduced in patients diagnosed with probable Alzheimer's disease. We also found that the decrease in volume correlated linearly with impaired global cognitive performance. These findings strongly suggest that, beside neo-cortical atrophy, deep grey matter structures in Alzheimer's disease suffer atrophy as well and that degenerative processes in the putamen and thalamus, like the hippocampus, may contribute to cognitive decline in Alzheimer's disease.